ASSESSING A SCHEMATA-DESIGNED READING MATERIAL IN AN EFL CLASS: STUDENTS’ NEEDS AND TEACHER EDUCATORS’ VOICE - AYU ENGGAR WATI; MISDI MISDI (State University of Medan, 2022)
This paper aims at assessing students’ needs of designed reading material for senior high school in Indonesia in improving their reading skills using schemata-based efl reading material. Designed in design-based research, this study involved EFL students and teacher educators as participants who recruited to participate voluntarily in this study. In designing the schemata-designed reading materials, the reading learning materials were revised based on the experts’ suggestions. The learning materials consist of three lessons. The first topic is about mammals. The second topic is about technology and the last is about landmarks. All of the lessons are about factual report text. The result reveals that students found their reading materials need to upgraded and teacher educators as experts’ judgment shows the designed-based reading material is categorized good.